Reconstruction of Congenital Lid defects - Muhammad Abid Latif, Muhammad Khalid, Muhammad Moin (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study the cosmetic results in congenital lid defect repairs. Material and Methods: Retrospective case series review of ten patients operated during the last five years (2006 to 2011). All patients with congenital lid defects were included. These included patients with colobomas of upper or lower lid and abortive cryptophthalmos. Reconstruction was done using rotation flaps or lid sharing procedures by a single surgeon. Results: Four patients underwent direct closure, four patients underwent Tenzel flap, one underwent composite graft and one underwent Cutler Beard flap. There were three patients with abortive cryptophthalmos who also underwent mucous membrane graft or conjunctival advancement. Three patients had good, four patients had satisfactory and three patients had poor results post-operatively. Three patients had dehiscence of wound after surgery which required further reconstruction. Exposure keratopathy due to delayed presentation was seen in three patients while cornea was scarred in three cases of abortive cryptophthalmos. Mild upper lid notch was seen in three patients and mild upper lid symblephron was seen in one patient. Conclusion: Early surgery with adequate sized advancement flap for closure is the key to good cosmetic result.